The crystal structure of 4–bromo-3,5-dinitropyrazole - Xiaolei Wang; Xianping Xin; Fanfan Sheng; Linxiu Zhao; Duanlin Cao; Fude Ren (Zeitschrift für Kristallographie - New Crystal Structures)
C3HBrN4O4, monoclinic, P21/c (no. 14), a = 11.9791(4) Å, b = 5.9291(2) Å, c = 9.8188(4) Å, β = 96.520(1)∘, V = 692.87(4) Å3, Z = 4, Rgt(F) = 0.0291, wRref(F2) = 0.0676, T = 170 K.